CULTIVATING OF POMEGRANATS AND THE PERSPECTIVES OF THIS BRANCH IN FERGANA REGION (Scientific journal of the Fergana State University, 2023)
In the article the information on the peculiar features of cultivating and growing of pomegranates along with the  perspectives  and development of  this sphere are given. The working process and future perspectives in  Ferghana region have been elucidated